A Year in Review: Key Milestones & Achievements of the European Journal of Geography in 2024 - Alexandros Bartzokas-Tsiompras; Kostis C. Koutsopoulos (European Journal of Geography)
The European Journal of Geography (EJG) Annual Report 2024 reflects on the pivotal role geography plays in addressing some of the most pressing challenges of our time, including climate change, urbanisation, geopolitical instability, and the rapid pace of digital transformation. The report highlights how geography continues to offer valuable insights and practical solutions for issues such as sustainable urban development, geography education, and societal transformation. In 2024, the journal published 24 thought-provoking articles spanning topics from urban geography to social inequality, underscoring its commitment to fostering meaningful interdisciplinary dialogue. As EJG’s global recognition grows, it continues to attract high-quality contributions and achieve notable success in major academic indexes. Looking ahead, the journal remains dedicated to advancing geographical research that addresses urgent European and global issues, welcoming new voices to shape the future of geography in 2025 and beyond.